2000
DOI: 10.1034/j.1600-0609.2000.90069.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis of defensins in blood and marrow neutrophils

Abstract: Polymorphonuclear neutrophils (PMN) are vital in host defense against microbial infections. This study provides a flow cytometric method for the quantitative analysis of microbicidal peptides (defensins) in cells of PMN lineage. Rabbit neutrophil peptides, NP-2 and NP-5, were measured in all PMN and in subpopulations of PMN expressing 1-selectin. PMN lineage counts were made on Wright's-stained blood smears and marrow cytospins. Immunoreactivity for NP-2, and NP-5 was detected by using the alkaline phosphatase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
(17 reference statements)
1
10
0
Order By: Relevance
“…Therefore, we calculated the ratios of elastase/neutrophil and lactoferrin/neutrophil and found that both were significantly increased compared with controls, suggesting that neutrophil degranulation was hyperstimulated and/or the granule content was enriched, turning neutrophils more prepared to inflammatory response. A stimulated granulocytopoiesis is usually associated with more immature circulating neutrophils, containing a higher number of elastase containing granules 29,30 . The release of these neutrophil activation products has to be counterbalanced by well‐known endogenous systems to reduce or to avoid the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we calculated the ratios of elastase/neutrophil and lactoferrin/neutrophil and found that both were significantly increased compared with controls, suggesting that neutrophil degranulation was hyperstimulated and/or the granule content was enriched, turning neutrophils more prepared to inflammatory response. A stimulated granulocytopoiesis is usually associated with more immature circulating neutrophils, containing a higher number of elastase containing granules 29,30 . The release of these neutrophil activation products has to be counterbalanced by well‐known endogenous systems to reduce or to avoid the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…30 Circulating mature neutrophils contain substantial amounts of the formed mature peptides, but are no longer transcribing their mRNA. 31 High levels of defensins in marrow neutrophils are associated with a high ratio of immature to mature neutrophilic granulocytes, 32 suggesting that the upregulation of defensin and protease mRNA expression in NA may represent the presence of immature neutrophils in the circulation. Under normal conditions granulocyte precursors do not leave the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…CHANGES IN PMN DEFENSINS DURING ENDOTOXEMIA 7797 (16). In the present study, a rise in defensins is likely due to maturational and/or conformational changes in the peptide precursors of less mature PMN.…”
Section: Vol 69 2001mentioning
confidence: 73%
“…Cells were then labeled (1 h) with a 1/50 dilution from stock of fluorescein isothiocyanate-conjugated anti-mouse secondary antibody (Sigma). After fixing with 0.8% PFA, and to exclude cell aggregates, cells were stained (15 min) with 4 g of propidium iodide per ml (16). The mean fluorescence intensity of 5,000 to 30,000 cells was measured using analysis gates for PMN in a flow cytometer (Epics XL; Beckman Coulter, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation